Three effective cases of transcatheter arterial embolization after atezolizumab and bevacizumab treatment for hepatocellular carcinoma: a case report - Koji Rinka; Kiyohide Kioka; Yuga Amano; Takashi Nakai; Yasuko Kawasaki; Norifumi Kawada (Journal of Medical Case Reports)
Abstract Background The Barcelona Clinic Liver Cancer staging system classifies hepatocellular carcinoma on the basis of tumor characteristics, liver function, and Eastern Cooperative Oncology Group performance status. Hepatocellular carcinoma is divided into five stages, and the treatment options for intermediate-stage hepatocellular carcinoma have evolved in recent years. Transcatheter arterial chemoembolization remains the standard treatment for intermediate-stage (stage B) hepatocellular carcinoma. However, the concepts of transcatheter-arterial-chemoembolization-unsuitable and transcatheter-arterial-chemoembolization-refractory tumors have emerged. The authors herein describe three Japanese patients with hepatocellular carcinoma who were treated with atezolizumab and bevacizumab followed by transcatheter arterial embolization or transcatheter arterial chemoembolization. Cases 1 and 2 were transcatheter-arterial-chemoembolization-unsuitable, and Case 3 was transcatheter-arterial-chemoembolization-refractory. All patients achieved a complete response, assessed according to the modified Response Evaluation Criteria in Solid Tumors guidelines. Case presentation The first patient was a 65-year-old Japanese man with a primary 11 cm hepatocellular carcinoma. He started treatment with atezolizumab and bevacizumab but developed grade 3 liver injury after two courses, leading to the discontinuation of these drugs and subsequent bland transcatheter arterial embolization. The second patient was an 82-year-old Japanese woman with multiple primary hepatocellular carcinomas. After one course of atezolizumab and bevacizumab, the treatment was interrupted because of grade 3 proteinuria. Bland transcatheter arterial embolization was performed after completing one course of atezolizumab and bevacizumab and one course of atezolizumab alone. The third patient was an 83-year-old Japanese man with recurrent multiple hepatocellular carcinomas. Despite 12 courses of atezolizumab and bevacizumab, the tumor in segment 4 of the liver increased in size and showed arterial-phase enhancement. Transcatheter arterial chemoembolization was performed to treat this tumor. All three patients achieved a complete response based on the modified Response Evaluation Criteria in Solid Tumors guidelines. Conclusion Atezolizumab and bevacizumab followed by transcatheter arterial embolization may be an effective treatment strategy for patients with intermediate-stage hepatocellular carcinoma that is transcatheter-arterial-chemoembolization-refractory or transcatheter-arterial-chemoembolization-unsuitable.